Oral hygiene habits, perceived barriers, and burden reported by caregivers of children and adolescents with disabilities - Orellana Herrera, Carla Andrea (2025)
Objetive: To determine oral hygiene habits, barriers, and burden reported by caregivers of children and adolescents with disabilities (CAD) in Talca, Chile. Materials and methods: A cross-sectional study was applied to caregivers of this vulnerable population. Children and adolescents were characterized using sociodemographic variables, diagnosis, and a degree of functional dependence, and their caregivers were characterized based on sociodemographic variables. Oral hygiene habits of CAD were determined along with the barriers faced by caregivers when maintaining oral hygiene on CAD and the burden reported by caregivers. Results: Out of 62 caregivers, 93.5% reported that CAD performed oral hygiene practices, either with or without assistance or supervision from the caregiver. Additionally, 91.4% used a manual toothbrush; 94.8% used toothpaste; 84.4% did not use dental floss; 84.5% did not use mouthwash; 50.0% brushed twice a day; and 75.7% of caregivers assisted CAD with their oral hygiene practices. Regarding barriers, 60.0% found it difficult to access all the areas of the CAD's mouth, and 49.1% identified anxiety in the child as a challenge during oral hygiene. Finally, 53.2% of caregivers experienced severe overload. Conclusions: Most caregivers reported that CAD engaged in oral hygiene practices and received assistance. They even reported that they faced barriers to performing children's oral hygiene and that they were severely overloaded.